Ruptured mature cystic teratomas mimicking advanced stage ovarian cancer: A report of 2 cases study - Suprasert P. (2014)
Spontaneous rupture of mature cystic teratoma is uncommon. Chronic rupture of teratomas may result in granulomatous peritonitis. In rare cases, the clinical presentation and the intraoperative findings may mimic those of advanced stage ovarian cancers. Two cases of ruptured mature cystic teratomas mimicking malignancy are reported in 50- and 53-year-old patients. Both presented with abdominal distension and weight loss. Elevation of serum CA-125 (233 unit/ml) was detected in one case. Intraoperative, nodular thickening of the omentum with marked peritoneal adhesion was observed in both cases. Ascites of 1500 ml was present in one case. Pathologic examination in both cases showed ovarian mature cystic teratomas with peritoneal granulomatous inflammations response to the released tumor content. Both patients were followed for 44 and 12 months and were free of symptoms without additional treatment other than surgery. Intraoperative pathologic consultation can help confirm the benign diagnosis and unnecessary major operation for malignancy can be avoided.